Adoption and use of technology with low litigation risk – the case of financial reporting on Twitter by ASX companies. Issue 10 (3rd October 2019) - Xiong, Feng; Chapple, Larelle; Xu, Si; Lin, Wenwei
ABSTRACT: Corporate adoption of technology faces challenges such as resource constraints and litigation risk. To investigate if low litigation risk encourages technology adoption and its use, this paper investigates corporate financial reporting on Twitter, a voluntary corporate disclosure practice without obvious litigation risk in Australia. This study reviews 4, 540 financial reporting related tweets from 222 ASX listed companies' Twitter accounts. An examination of tweet sentiment reveals a positive reporting bias, as listed companies are more willing to disclose positive financial reporting information on Twitter . A comparison of corporate financial reporting tweets prior to and after 2013 reveals that use of Twitter for opportunistic voluntary disclosure is gaining popularity, a trend that warrants close attention by regulators in order to protect investors from selective disclosure with reporting bias.